An Analysis upon Socio - Cultural Awakening and Religious Reform Movements in 19th Century India: Unveiling the Dynamics of 19th Century Social and Religious Movements in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Social movements primarily take the form of non-institutionalised collective political action which strive for political and /or social change. While India has witnessed many such movements over the centuries, it is only recently that scholars have begun to study them in depth. Due to caste based hierarchy in society and Brahmins’ domination, many of the reform movements were taken place in India. The main philosophies behind these movements were gender and caste based equality and unique worship to single god. These movements emphasized social equality and humanity.